PENYESUAIAN TARIF JASA PELAYANAN BAHAN BAKU KERAMIK BL-1 DAN K-5 BERBASIS ELEMEN BIAYA TAHUN 2017 PADA BALAI TEKNOLOGI INDUSTRI KREATIF KERAMIK - I Nyoman Normal; Wiryawan Suputra Gumi (Forum Manajemen, 2018)
The aims of this research is adjust the ceramics raw material service tariff of BL-1 and K-5 based on 2017 cost element. The results shew that: (1) the tariff of ceramic raw material services BL-1 and K-5 are Rp 5.993,95 and Rp 3.802,28 each kg. For the BL-1 followed by cost of goods manufactured Rp 4.610,73, expected profit margin Rp 1.383,22, and operating expense Rp 691,61 (marketing expense Rp 414,97 and general & administrative expense Rp 276,64). For the K-5 followed by cost of goods manufactured Rp 2.924,83, expected profit margin Rp 877,45, and operating expense Rp 438,72 (marketing expense Rp 263,23 and general & administrative expense Rp 175,49); and (2) the tariff of ceramic raw material services BL-1 and K-5 influence of cost of goods manufactured BL-1 and K-5. The tariff of ceramic raw material services BL-1 and K-5 according to government regulation number 6 in 2015 produce cost of goods manufactured BL-1 and K-5 Rp 1.923,07 each kg, that followed by raw material cost Rp 1.459,80, direct labor cost Rp 176,73, variable overhead cost Rp 92,88, and fixed overhead cost Rp 193,66. The actual cost of goods manufactured BL-1 and K-5 smaller about Rp 2.687,66 each kg for BL-1 and Rp 1.001,76 each kg for K-5 than theoretically; and (3) The actual gross profit, operating profit, and net profit ceramics raw material service of BL-1 smaller about Rp 806,29, Rp 403,15, and Rp 322,52 each kg than theoretically, and for the K-5 smaller about Rp 300,52, 150,26, and Rp 120,21 each kg than theoretically.